2018
DOI: 10.1074/jbc.ra118.003990
|View full text |Cite
|
Sign up to set email alerts
|

Plasminogen activation triggers transthyretin amyloidogenesis in vitro

Abstract: Systemic amyloidosis is a usually fatal disease caused by extracellular accumulation of abnormal protein fibers, amyloid fibrils, derived by misfolding and aggregation of soluble globular plasma protein precursors. Both WT and genetic variants of the normal plasma protein transthyretin (TTR) form amyloid, but neither the misfolding leading to fibrillogenesis nor the anatomical localization of TTR amyloid deposition are understood. We have previously shown that, under physiological conditions, trypsin cleaves h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
88
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 77 publications
(89 citation statements)
references
References 24 publications
1
88
0
Order By: Relevance
“…While the epidemiological association between CTS and CA is well established, the underlying mechanisms remain unclear. The reason for these two tissues being exclusively involved, as well as the observed temporal delay between the two remain unexplained, but it has been suggested that a repeated mechanical stimulus on tendons and myocardium could favour fibrillogenesis and/or tissue infiltration . Our retrospective study was not designed to explore the mechanistic relationship between CTS and CA and did not include a histological analysis of the tenosinovial tissue of patients who underwent CTS surgery.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While the epidemiological association between CTS and CA is well established, the underlying mechanisms remain unclear. The reason for these two tissues being exclusively involved, as well as the observed temporal delay between the two remain unexplained, but it has been suggested that a repeated mechanical stimulus on tendons and myocardium could favour fibrillogenesis and/or tissue infiltration . Our retrospective study was not designed to explore the mechanistic relationship between CTS and CA and did not include a histological analysis of the tenosinovial tissue of patients who underwent CTS surgery.…”
Section: Discussionmentioning
confidence: 99%
“…The reason for these two tissues being exclusively involved, as well as the observed temporal delay between the two remain unexplained, but it has been suggested that a repeated mechanical stimulus on tendons and myocardium could favour fibrillogenesis and/or tissue infiltration. 28 Our retrospective study was not designed to explore the mechanistic relationship between CTS and CA and did not include a histological analysis of the tenosinovial tissue of patients who underwent CTS surgery. The presence of TTR amyloid in the tenosinovium of patients with CTS has been previously demonstrated (online supplementary Table S8), [10][11][12][13]29 but the co-existence of CA has been rarely investigated, and when it has, the prevalence was found to be particularly low.…”
Section: Discussionmentioning
confidence: 99%
“…The advantages of this method are that it is easy to apply in highly aggregated systems, it has a low-cost, and it has high reproducibility. As relevant examples, we can mention actin polymerization kinetics, hemoglobin fibrillation [ 74 ] and liquid phase separation of TDP-43 C-terminal domain [ 75 ], alpha-synuclein aggregation and its effects on Tau protein [ 76 ], TTR amyloid aggregation in the presence of plasminogen [ 77 ], and the ÎČ-amyloid peptide [ 78 ]. From a pharmaceutical point of view, it is employed to evaluate the effect of stirring on the aggregation processes of an antibody, in the presence or absence of polysorbate 80 by using turbidity measurements (at 350 and 550 nm) [ 79 ].…”
Section: Uv-vis Absorption Spectroscopy and Turbidity Are Initial mentioning
confidence: 99%
“…Bellotti’s group has recently discovered that disassembly of TTR and fibrillogenesis can be achieved under physiologic conditions by mechano-enzymatic mechanism consisting of a proteolytic cleavage permitted by the perturbation of the folded state in the presence of physiologic biomechanical forces [ 149 , 150 ]. Fibrils formed through this procedure display chemical and structural properties extremely similar to those extracted from natural deposits and highlight the role of a truncated form of TTR [ 149 ] in priming the amyloidogenesis.…”
Section: The Main Classes Of Anti-amyloid Compoundsmentioning
confidence: 99%